Raging Hormones: Why Age-Based Etiological Conceptualizations of the Development of Antisocial Behavior Are Insufficient - White, Stuart F.; Estrada Gonzalez, S. Mariely; Moriarty, Eibhlis M. (Frontiers in Behavioral Neuroscience, 2022)
Developmental science, particularly developmental neuroscience, has substantially influenced the modern legal system. However, this science has typically failed to consider the role of puberty and pubertal hormones on development when considering antisocial behavior. This review describes major theoretical positions on the developmental neuroscience of antisocial behavior and highlights where basic developmental neuroscience suggests that the role of puberty and pubertal hormones should be considered. The implications of the current state of the science with respect to developmental neuroscience is considered, particularly what is known in light of development beyond puberty. This review shows that development continues to an older age for many youth than the legal system typically acknowledges. The plasticity of the brain that this continued development implies has implications for the outcome of interventions in the legal system in ways that have not been explored. Future directions for both developmental scientists and legal professions are recommended.